Asymmetric price adjustments: A supply side approach - Fabio Antoniou; Raffaele Fiocco; Dongyu Guo (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2015)
Using a model of dynamic price competition, this paper provides an explanation from the supply side for the well-established observation that retail prices adjust faster when input costs rise than when they fall. The opportunity of profitable storing for the next period induces competitive firms to immediately increase their prices in anticipation of higher future input costs. This relaxes competition and firms earn positive profits. Conversely, when input costs are expected to decline, firms adjust their prices only after a cost reduction materializes, and the firms' incentives for price undercutting lead to the standard Bertrand outcome.
urn:nbn:de:bvb:19-epub-23804-0
Keywords: D4; L1; 330; Asymmetric price adjustments; Bertrand-Edgeworth competition; Storage; Gasoline